Indonesian Adaptation and Validation of The Child-Adolescent Perfectionism Scale – Short Form (CAPS-SF) - Sonia Marcellina; Fitriani Yustikasari Lubis (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
This study aimed to adapt and examine the psychometric properties of The Child-Adolescent Perfectionism Scale – Short Form (CAPS – SF) in an Indonesian sample. In Indonesia, research on perfectionism is being developed, but there is no measurement for adolescent perfectionism that can be used. Therefore, a valid and reliable measurement is needed. The Child-Adolescent Perfectionism  Scale – Short Form (CAPS – SF) developed by Bento et al. is an instrument consisting of 2 dimensions of Socially Prescribed Perfectionism and Self-Oriented Perfectionism with a total of 9 items that can measure perfectionism in children and adolescents. The adaptation process followed the guidelines established by the International Test Commission such as translation, cognitive interview, and test of the pre-final Indonesian version which involved 322 adolescents aged 13-15 years who lived in Indonesia. Reliability test using Cronbach's Alpha and CFA, which was used to measure the construct validity, showed that the nine items in adapted The Child-Adolescent Perfectionism Scale – Short Form (CAPS – SF) could be used to measure the perfectionism of Indonesian adolescents.